Which values of p and q would make the value of the following expression equal to 29i? (2 – 5i)(p + q)i A.p = 2, q = 5i B.p = –2, q = 5i C.p = 2, q = –5i D.p = –2, q = –5i

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Which values of p and q would make the value of the following expression equal to 29i? (2 – 5i)(p + q)i A.p = 2, q = 5i B.p = –2, q = 5i C.p = 2, q = –5i D.p = –2, q = –5i

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

expand first: (2 – 5i)(p + q)i =
Okay @SolomonZelman could probably explain exactly how to do this because he is smart like that but I was able to pass the SAT by plugging these things in so lets start with A.
(2-5i)(2+5i)i 4 - 10i + 10i - 25i^2 4 - 10i + 10i - 25(-1) 4 - 0i - (-25) 4 + 25 29

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

@SolomonZelman just check my problem on A so I know I am not giving @dreamstoogood wrong info.
u need it to equal 29i, not 29
o.o What did I do wrong?
(2 – 5i)(p + q)i=29i (in a+bi form, it is 0+29i) (2 – 5i)(p + q)i = expands to >> 2p+2q-5pi-5qi so, 2p+2q-5pi-5qi=29i in a+bi form, (2p+2q)+(-5p-5q)i=0+29i therefore 2p+2q=0 (-5p-5q)i=29i
so there is a system of equations to solve
you can cancel i' in equation 2, and from that point and on it is just algebra.

Not the answer you are looking for?

Search for more explanations.

Ask your own question